2020
DOI: 10.1007/s12070-020-01982-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Determining Tracheostomy Decannulation Failure Rate in Adults: An Indian Perspective Descriptive Study

Abstract: Decannulation is an essential step in liberating tracheostomised patients from mechanical ventilation. This procedure is purely based on the clinician’s judgment and there is no universally accepted protocol to date for this vital procedure. This study aimed to describe decannulation practice and failure rates in patients with tracheostomy and to determine the factors associated with the outcome of tube removal. A prospective study was done on 50 patients (both sexes) who required a tracheostomy and cared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The preoperative endoscopic assessment showed that the maximum number of patients had grade-III stenosis (grade III: IV ¼ 10:3) and that, infrastomally, 10 healthy rings were present (median of 10 with a range of [8][9][10][11][12][13][14]. The vocal cords were mobile in all the patients assessed.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The preoperative endoscopic assessment showed that the maximum number of patients had grade-III stenosis (grade III: IV ¼ 10:3) and that, infrastomally, 10 healthy rings were present (median of 10 with a range of [8][9][10][11][12][13][14]. The vocal cords were mobile in all the patients assessed.…”
Section: Resultsmentioning
confidence: 96%
“…9 In a study by Bishnoi et al, the factors affecting decannulation were lack of swallowing/secretions/cough management and the development of stridor. 10 Further research is necessary to determine the risk factors for the development of postintubation stenosis and to develop guidelines regarding the timing of tracheostomy in intubated patients. Moreover, future studies are needed to assess patient outcomes in terms of both subjective and objective parameters to provide surgeons with a comprehensive interpretation of the results of the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed recannulation in four of 28 subjects, exceeding 2-5% which is considered an acceptable recannulation rate [20]. A recent study including 50 patients demonstrated a similar rate [11]. The wide variation in failure rates may be due to a lack of agreement on the time-point for assessing failure [23].…”
Section: Decannulation Failurementioning
confidence: 83%
“…Many patients require frequent wound care due to bandage blow off or accumulation of pulmonary secretions around the stoma site [ 10 ]. Hygiene challenges associated with airway secretion may increase the risk of airway infection and respiratory failure, and may therefore heighten the risk of relapse to ventilator therapy [ 8 , 11 , 12 ]. Simple suturing of the skin has not proven effective and even entails a risk of subcutaneous emphysema.…”
Section: Introductionmentioning
confidence: 99%